Kontekstualisasi Prinsip Kekuasaan sebagai Amanah dalam Pertanggungjawaban Presiden dan Wakil Presiden Republik Indonesia - Hakiki, Yuniar Riza (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to analyze the contextualization of the principle of power as a mandate in institutionalizing the accountability of the President according to the 1945 Constitution of the Republic of Indonesia. This research is normative juridical, which uses secondary data. The study found that the contextualization of the principle of power as a mandate in the accountability of the President/Vice President of the Republic of Indonesia is institutionalized through a number of provisions stipulated in the 1945 Constitution of the Republic of Indonesia, including: (1) the responsibility of the President in the event of a dispute over authority between State Institutions in the Constitutional Court, as accountability for the implementation of its authority; (2) the responsibility of the President if he is suspected of violating the law and the constitution, as accountability for the actions committed; (3) The President is also responsible in cases of judicial review of the Constitution, as his responsibility in forming and enacting laws; (4) The President is also responsible in cases of reviewing statutory regulations under the Act against the Law, as his responsibility in forming and enacting laws; and (5) political accountability directly to the people